Efektivitas Teknik Menyikat Gigi Vertikal Horizontal dan Kombinasi terhadap Indeks Plak pada Penghuni Wisma - Rustam, Aldi Rivaldi; Adawiyyah, Evi; Mansjur, Karima Qurnia; Rani, Nur Aedah Ahmad (Jurnal Terapi Gigi dan Mulut, 2025)
This study was motivated by the low level of awareness regarding dental health and proper toothbrushing techniques among students, leading to high plaque indices. This study aimed to evaluate the effectiveness of vertical, horizontal, and combined toothbrushing techniques in reducing plaque indices among students residing in Dormitory 2 at Hasanuddin University. The study employed a pre-experimental design with a pre-test and post-test approach. The sample consisted of 73 students divided into three groups based on the brushing technique applied. Data were collected through plaque index measurements before and after the intervention using the Personal Hygiene Performance (PHP) method. The results indicate that all three toothbrushing techniques effectively reduce plaque indices, with the highest average reduction observed in the group using the combination technique. Before treatment, the average score was 2.5, categorized as moderate, which decreased to 0.8 (good category) after treatment. The vertical technique had an average score of 2.7 (moderate) before treatment, decreasing to 1.8 (moderate) afterward. The horizontal technique had an average score of 2.0 (moderate) before treatment, which decreased to 1.6 (good) after treatment.